Aplicando técnicas de recomendação em sistemas de ajuda em pares - Müller, Luana (2013)
Despite help systems have been considered a way to help users to better understand and use applications in general, users are still resistant in using them. Aiming to promote and encourage their use, peer help systems promote aid from applications users through the formation of pairs of users that will interact to complement the assistance provided by online help system. In this context, this study aims to support the process of users search and selection to form these pairs using recommender systems and, thus, try to qualify users understanding about the environment where they are inserted. In this regard, it was proposed a selection process of pairs that use similarity index and relevant criteria mentioned by users. This process was directed to a collaborative learning environment that was chosen because it is growing and has a wide range of user profiles and tasks making it a fertile environment for the implementation of a help system. The proposed process was implemented in a prototype of a peer help system, allowing the analysis of the pair formation that was made and thus getting information about the effectiveness of its use, and therefore making it possible to analyze the potential of the use of recommendation techniques with the process of forming pairs.